2022
DOI: 10.1007/s10639-022-11273-4
|View full text |Cite
|
Sign up to set email alerts
|

Social inclusion as a perspective for the validation of the "DigCompEdu Check-In" questionnaire for teaching digital competence

Abstract: Making use of digital technologies and all the possibilities that benefit education is one of the objectives of the European Framework for the Digital Competence of Educators, as well as their potential for personal development and social inclusion, among other aspects. The aim of this study was to validate the «DigCompEdu Check-In» scale as an instrument for the self-reflection of educators regarding their digital competence from the perspective of social inclusion. This questionnaire provides a more accurate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…Santos et al, , 2021b. São diversos os trabalhos que buscam validá-lo (Cabero-Almenara et al, 2020;Cabero-Almenara, Guillén-Gámez, et al, 2021;Cabero-Almenara, Gutiérrez-Castillo, et al, 2021;Cabero-Almenara et al, 2022;Martín-Párraga, Llorente-Cejudo, & Cabero-Almenara, 2022), bem como o seu instrumento nativo, o DigCompEdu CheckIn 2019 (Cabero-Almenara et al, 2022;Gallardo-Echenique et al, 2023;Ghomi & Redecker, 2019;Llorente-Cejudo et al, 2022;Martín-Párraga, Llorente-Cejudo, & Barroso-Osuna, 2022).…”
Section: Figuraunclassified
“…Santos et al, , 2021b. São diversos os trabalhos que buscam validá-lo (Cabero-Almenara et al, 2020;Cabero-Almenara, Guillén-Gámez, et al, 2021;Cabero-Almenara, Gutiérrez-Castillo, et al, 2021;Cabero-Almenara et al, 2022;Martín-Párraga, Llorente-Cejudo, & Cabero-Almenara, 2022), bem como o seu instrumento nativo, o DigCompEdu CheckIn 2019 (Cabero-Almenara et al, 2022;Gallardo-Echenique et al, 2023;Ghomi & Redecker, 2019;Llorente-Cejudo et al, 2022;Martín-Párraga, Llorente-Cejudo, & Barroso-Osuna, 2022).…”
Section: Figuraunclassified
“…Hatlevik [25] determinó la capacidad del estudiante en el uso de herramientas digitales a partir de la gestión de la información, las competencias tecnológicas y las habilidades de comunicación y de organización, y demostró que el estudiante con mayores capacidades presenta mejor desempeño en su proceso formativo. De igual forma, Llorente-Cejudo et al [26] definió que la presencia, el acceso y el uso de las tecnologías inciden favorablemente en las competencias digitales del estudiante. La evaluación de las habilidades digitales permite, por un lado, verificar si los estudiantes poseen las capacidades necesarias para adaptarse a los entornos educativos y, por el otro, diseñar estrategias que garantice el conocimiento que requieren los estudiantes para mantener un proceso de enseñanza y aprendizaje exitoso.…”
Section: Introductionunclassified
“…Recent systematic reviews have shown the increasing interest to analyze digital competences in HE settings (Basilotta-Gómez-Pablos et al, 2022;Zhao et al, 2021). Most of these studies are based on the European Framework for the Digital Competence of Educators (DigCompEdu), which is articulated around six competence areas that teachers must develop to promote effective, inclusive, and innovative learning strategies, using digital tools (Caena and Redecker, 2019;Llorente-Cejudo et al, 2022;Lu et al, 2021;Punie and Redecker, 2019).…”
Section: Introductionmentioning
confidence: 99%